Analysis of Sambucus ebulus L. (dwarf elder) fruit extracts for their chemical composition and antioxidant potential, as well as their antibacterial activity against Trichophyton rubrum (Castell.) Sabour and other microorganisms (International Journal of Life Sciences Biotechnology and Pharma Sciences, 2021)
Purpose and Background: Sambucus ebulus L. has a long history of use in Anatolian traditional medicine. Based ontraditional use, this research aims to explore the phytochemical composition, antibacterial activities, and antioxidantactivities of S. ebulus fruit extracts, as well as their antifungal capabilities against Trichophyton rubrum (Castell.)Sabour.The fruits of S. ebulus were used to make two different extracts. We used LC-MS/MS to determine the phytochemicalmakeup of the fruit extracts of S. ebulus. We used the broth microdilution technique to test the antibacterial activityagainst a panel of microorganisms. Furthermore, the disc diffusion technique was used to assess the antifungal activityof S. ebulus extracts against three yeasts and T. rubrum in vitro.The main components found in the dried fruit methanol extract (DFM) were identified as hederagenin (5.38±0.4949μg/g) and fumaric acid (3.06±0.0275 μg/g). The most prevalent ingredient in the fresh fruit juice (FFJ) was found tobe fumaric acid, with a concentration of 3.97±0.0357μg/g. The extracts included hitherto unseen compounds includingacacetin, chrysin, eupatilin, hederagenin, isosakuranetin, myricitrin, and rhamnocitrin. Both E. coli and Candidatropicalis were moderately inhibited by DFM, with MIC values of 625 mg/L and 312.5 mg/L, respectively. Bothextracts were ineffective against Staphylococcus aureus and Proteus mirabilis, with MIC values of 1250 mg/L;however, T. rubrum proved to be resistant to both extracts. The antioxidant capacity of the extracts was measuredusing the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical cleaning technique. With an IC50 value of 5.941±0.236µg/mL and 7.893±0.939 µg/mL, respectively, DFM and FFJ demonstrated potent antioxidant activity against DPPHradicals.In conclusion, our findings demonstrated that S. ebulus fruits could not be used in antifungal topical formulations,despite the fact that locals use them to cure nail fungus (onychomycosis). Furthermore, the antibacterial activityoutcome is consistent with previous research in this area.